International student mobility: a comparative study between Indian and Italian students in London - Anastasio, Marina (2023)
The aim of this thesis is to explore international student mobility in current times within the changing landscape in higher education in the UK. Although this time period corresponds to increasing international student mobility in the UK, the lived experiences of international students are little known. For this reason, central to the study is the understanding of international students studying and living in a specific UK context, namely Greater London, which is both the region where there is the highest concentration of foreign students in the UK, and one of greatest ones worldwide. In order to construct a more holistic understanding of international student mobility, the study explores some key themes, including: external dimensions (i.e. social, cultural, political, and economic aspects), and more individual dimensions (i.e. psychological, emotional and cognitive aspects). This research is an attempt to bring together these different dimensions to illuminate the complexity and the heterogeneity of international student mobility. In order to provide further understanding of the dimensions encompassing international student mobility, a qualitative approach is adopted. The qualitative design includes repeated interviews with two groups of international students studying in London: a group made of international students from a non-EU country (India), and a group made of international students from a EU country (Italy). In this study repeated interviews with the same informants over a five-year period of time are used to identify themes and changes over time in the informants’ feedback. This thesis represents a contribution to international student mobility’s literature by uncovering international students’ lived experiences and subjectivities. It stresses the importance of seeking to understand international students’ views, perspectives, and the variety of ways they deal with their mobile experiences. The research findings suggest that, although there are some differences between participants, their understanding and the strategies they adopt to cope with their realities, can influence and shape international student mobility.